2019
DOI: 10.3390/ijerph16234680
|View full text |Cite
|
Sign up to set email alerts
|

Early Waning of Maternal Measles Antibodies in Infants in Zhejiang Province, China: A Comparison of Two Cross-Sectional Serosurveys

Abstract: In China, children aged <8 months, who were expected to be protected by maternal antibodies before receiving the first dose of measles vaccine, were the age group with the greatest risk of infection in recent years. In this study, we evaluated whether infants yet to be age-eligible for measles vaccine had a sufficient seropositive level of maternal measles antibodies in 2009 and 2013. Blood samples were collected from infants aged <8 months through population-based serological surveys conducted in Zhejiang, Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
2
8
0
Order By: Relevance
“…Therefore, the role of rotavirus vaccines is also important. Moreover, increased risk of disease in younger children might be due to naive immune system in children of younger ages and waning of maternal antibodies [16][17][18][19][20][21]. The finding of this study is also in line with studies done in Benishangul region, Eastern Ethiopia, Enderta Woreda, Wolitta Soddo and southern Ethiopia [4,7,[22][23][24][25].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Therefore, the role of rotavirus vaccines is also important. Moreover, increased risk of disease in younger children might be due to naive immune system in children of younger ages and waning of maternal antibodies [16][17][18][19][20][21]. The finding of this study is also in line with studies done in Benishangul region, Eastern Ethiopia, Enderta Woreda, Wolitta Soddo and southern Ethiopia [4,7,[22][23][24][25].…”
Section: Discussionsupporting
confidence: 87%
“…The effect of number of under-five children in the household on childhood diarrhoea varies by current age of mothers. Number of under-five children affects the occurrence of diarrhoea differently in older age mothers (35-49) versus younger age mothers (15)(16)(17)(18)(19)(20)(21)(22)(23)(24). The odds of the occurrence of diarrhoea for three or more number of under-five children (relative to two or less number of under-five children) in older age mothers was 4.7 times as high as in younger age mothers.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic literature review revealed that slower waning of maternal antibody in infants occurred in high disease burden settings than in sustained elimination settings and low burden settings. 22 Similarly to sustain elimination settings like Ontario, Canada 18 and Belgium, 19 a significant loss of measles protection by 3 months of age was observed in the non-elimination settings of Zhejiang, 23 Wuxi, 20 Tianjin, 11 Shufu (our study), China. Over decades, China has made great efforts to eliminate measles.…”
Section: Discussionsupporting
confidence: 57%
“…The effect of number of under-five children in the household on childhood diarrhoea varies by current age of mothers. Number of under-five children affects the occurrence of diarrhoea differently in older age mothers (35-49) versus younger age mothers (15)(16)(17)(18)(19)(20)(21)(22)(23)(24). The odds of the occurrence of diarrhoea for three or more number of under-five children (relative to two or less number of under-five children) in older age mothers was 4.7 times as high as in younger age mothers.…”
Section: Discussionmentioning
confidence: 99%